The Prohibition of Riba in Islam - M. Umer Chapra (International Institute of Islamic Thought, 2021)
A number of objections have been raised against the prohibition of riba (interest) in Islam and it has been alleged that a riba-free economy will face so many problems that it may not be able to survive. This paper evaluates the nature and significance of some of the major objections and, in the process, also indicates the rationale behind the prohibition of riba. I. ALLOCATION OF RESOURCES One of the objections raised against an interest-free economy is that it will not be able to bring about an optimum allocation of resources. The reason given for this is that interest is a price and like all prices it performs the function of allocating 'scarce' loanable funds among the 'infinite' users of such funds in an objective manner on the basisof ability to pay the price. If the demand for, or supply of, loanable funds changes, a new equilibrium is reached at a different rate of interest. This objection is based on two assumptions. The first assumption is that in the absence of interest loanable funds will be available ‘free’ to borrowers, the demand will thus be infinitely large and there will be no mechanism for equating demand with supply. This implies that interest is the only objective criterion for allocation of resources and, in its absence, scarce financial resources will be used inefficiently to the detriment of society. The second assumption is that the money rate of interest has been a successful mechanism in allocqting resources optimally and that profit cannot perform the function efficiently. The first asumption is baseless because funds will not be available ‘free’ in the Islamic system. They will be available at a cost, and the cost will be the ‘share’ in profit. The rate of profit will hence become a criterion for allocation of resources as well as the mechanism for equating demand with supply. The greater the expected or ex-ante rate of profit in any business, the greater may be the supply of funds to that business. If the actual or ex-post profit for certain businesses is consistently lower than the ex-ante profit such businesses may face difficulty in raising funds in the future. Therefore, while ex-ante profit will be immediately important in determining the flow of investment, the ex-post performance will be crucial for the future success of the business in raising funds. This should help enforce a greater discipline in investments through a more careful evaluation of projects, weeding out all inefficient and unproductive projects. This is not the same in interestbased investment. The interest-oriented lender does not share in the risk of the business financed. He shifts the entire risk of busines to the entrepreneur and assures himself of a predetermined rate of return irrepwtive of the ultimate net outcome of the borrower’s business. He thus does not have to undertake as thorough an evaluation as the sahib al-mal (financier) would have to undertake in a riba-free economy, either by himself or with the help of a bank or consulting firm. Because of a twosided evaluation of projects, the rate of profit in the Islamic system should be a more efficient mechanism for allocation of resources than interest can ever be in the capitalist system ...